2021
DOI: 10.1039/d1nh00113b
|View full text |Cite
|
Sign up to set email alerts
|

Bonding, structure, and mechanical stability of 2D materials: the predictive power of the periodic table

Abstract: Inverse dependence of 2D covalent bonding on bond length of elemental and isoelectronic binary monolayers of the main group elements II–VI. This behavior is also observed for the Young's modulus and ultimate strength.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 282 publications
(437 reference statements)
5
29
0
Order By: Relevance
“…Since we also found that the phonon band structure of a 2 × 2 × 1 supercell of SrTiO 3 -ML calculated using SCAN + rVV10 exhibits imaginary phonon modes which disappear only for a 1 × 1 × 1 supercell, this γ γ β can be due to the presence of electrostatic potential between A 2 O and ASn layers whose influence enhances with increasing size of the supercell and cannot fall to zero for an infinite vacuum [25,94]. Similar negative phonon modes are also reported in earlier DFT studies for large supercell calculations of perovskitetype MLs [25,27,16]. To this end, we resort to further examining the thermodynamic stability of the A 3 SnO-MLs that can be assessed in terms of the surface energy, , which should be a small positive value [16,[95][96][97].…”
Section: Thermodynamic Stability Of a 3 Sno-mlsupporting
confidence: 74%
See 1 more Smart Citation
“…Since we also found that the phonon band structure of a 2 × 2 × 1 supercell of SrTiO 3 -ML calculated using SCAN + rVV10 exhibits imaginary phonon modes which disappear only for a 1 × 1 × 1 supercell, this γ γ β can be due to the presence of electrostatic potential between A 2 O and ASn layers whose influence enhances with increasing size of the supercell and cannot fall to zero for an infinite vacuum [25,94]. Similar negative phonon modes are also reported in earlier DFT studies for large supercell calculations of perovskitetype MLs [25,27,16]. To this end, we resort to further examining the thermodynamic stability of the A 3 SnO-MLs that can be assessed in terms of the surface energy, , which should be a small positive value [16,[95][96][97].…”
Section: Thermodynamic Stability Of a 3 Sno-mlsupporting
confidence: 74%
“…In the backdrop of rapid discoveries in the 2D realm, little attention has unfortunately been paid to the 2D derivatives of perovskite-type materials, which are otherwise known to display a wide range of functional physical properties in their bulk form that are tunable to specific applications by manipulating their structure [15]. This can mainly be attributed to the fact that research efforts for 2D materials have been inspired by the mechanical exfoliation technique [16][17][18] and, therefore, exploring 2D layers of strongly bound bulk perovskites has remained a sort of "no-man's-land" since it is not possible to peel-off single layers. In addition, it was earlier believed that 2D limits of isotropically bonded perovskites are unachievable as a structural collapse below a critical film thickness of 5 unit cells (UC) would be triggered [19].…”
Section: Introductionmentioning
confidence: 99%
“…At present, two-dimensional materials are considered as one of the most promising materials for next-generation nanoelectronics and nanophotonics [121,122]. The family of two-dimensional crystals includes dielectrics (for example, hexagonal boron nitride and transition metal oxides), topological insulators (bismuthene telluride), semiconductors (molybdenum and tungsten disulfides), semimetals (graphene), metals (titanium disulfide), and superconductors (niobium diselenide) [3,4].…”
Section: Brief Outlook Into the Perspectives Of Single-element 2d Mat...mentioning
confidence: 99%
“…Detailed understanding of the bonding behavior of elemental monolayers allows a useful prediction of bonding in the large family of their binary, e. g., SiC, and isoelectronic compounds, e. g., h-BN, by taking the mean values of binding energies and bond lengths of the two constituents. 4 The diagrams of the cohesive energy and bond length versus period number and column number reveal the two main factors controlling type and strength of 2D bonding and structure of main-group II-VI monolayers. Covalent 2D bonding depends on the inherent periodicity of atom size of the columns, mostly following the tabulated van der Waals diameter.…”
mentioning
confidence: 96%
“…[ 1 , 3 ] Besides the main‐group elements theory already covers a large number of their binary and isoelectronic compounds. [4] Only limited information on structural properties and mechanical behavior comes from the few synthesized free‐standing monolayers and the steadily increasing number of adsorbed monolayers grown on stabilizing surfaces.…”
mentioning
confidence: 99%